Shoulder pain - a common problem in world-class badminton players - Fahlström, M.; Yeap, J. S.; Alfredson, H.; Söderman, K. (Scandinavian Journal of Medicine & Science in Sports, 2006)
Badminton is a sport that requires a lot of over-shoulder motion, with the shoulder in abduction/external rotation. This questionnaire study on 188 international top-level badminton players during the World Mixed Team Championships showed that previous or present shoulder pain on the dominant side was reported by 52% of the players. Previous shoulder pain was reported by 37% of the players and on-going shoulder pain by 20% of the players. There were no significant differences in the prevalence of shoulder pain between men and women. The majority of the shoulder pain had started gradually. The pain was usually associated with shoulder activity, and stiffness was a common, associated symptom. Furthermore, the shoulder pain was associated with consequences such as sleeping disturbances, changes in training and competition habits, and it also affected activities of daily living. The majority of the players had sought medical advice and had been given different kinds of treatment. The study showed that shoulder pain is a common and significant problem in world-class badminton players, and the consequences are most likely of importance for their training and playing capacity.